2006
DOI: 10.2527/2006.841162x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of refined coconut oil or copra meal on methane output and on intake and performance of beef heifers1

Abstract: An experiment was conducted to establish the effect of feeding either refined coconut oil (CO) or copra meal containing CO to beef heifers on DMI, animal performance, enteric CH4 emissions, diet digestibility, and the fatty acid profile of the resulting meat. Forty-one Charolais and Limousin crossbred beef heifers (474 +/- 29 kg; 661 +/- 89 d of age) were blocked by BW before being assigned in a randomized complete block design to 1 of 3 experimental treatments (n = 12) or to a pretrial slaughter group (n = 5)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
56
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(73 citation statements)
references
References 24 publications
13
56
0
2
Order By: Relevance
“…This could explain the variability of the effects of these additives on protozoa concentration. As an example, lipid effect on protozoa is dependent on the fatty acid profile, with a higher effect of medium chain fatty acids than polyunsaturated ones, which was confirmed by our data: lauric acid tended to reduce protozoa more markedly than polyunsaturated fatty acids (Jordan et al, 2006). Defaunation studies did not necessarily observe a reduction of CH 4 emission.…”
Section: Discussionsupporting
confidence: 78%
“…This could explain the variability of the effects of these additives on protozoa concentration. As an example, lipid effect on protozoa is dependent on the fatty acid profile, with a higher effect of medium chain fatty acids than polyunsaturated ones, which was confirmed by our data: lauric acid tended to reduce protozoa more markedly than polyunsaturated fatty acids (Jordan et al, 2006). Defaunation studies did not necessarily observe a reduction of CH 4 emission.…”
Section: Discussionsupporting
confidence: 78%
“…However, the high coefficient of variation (30.03 to 65.38) may have influenced the results. Many studies show the reduction of methane when using fat in the diet (CASTAGNINO et al, 2014;JOHNSON;JOHNSON, 1995;JORDAN et al, 2006;JORDAN et al, 2007;MACHMÜLLER;KREUZER, 1999;O'BRIEN et al, 2014;SOLIVA et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…If the industrial oil extraction process is not efficient, high quantities of coconut oil can stay in copra meal and influence the ruminal fermentation of this ingredient. A reduction in methane production can be obtained when refined coconut oil is used in diets (JORDAN et al, 2006;JORDAN et al, 2007;MACHMÜLLER;KREUZER, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…to ruminant diets has been shown to reduce methane production between 18 % and 62 % in Rusitec fermenters (Dohme et al 2000 ), sheep (Ding et al 2012 ), beef cattle (O'Mara 2004 ;McGinn et al 2004 ;Beauchemin and McGinn 2006 ) and dairy cows (Hristov et al 2009 ;Sejian et al 2011b ;Brask et al 2013 ). Copra meal gives comparable decreases in CH 4 to refi ned coconut oil (Jordan et al 2006 ). Comparison of the effects of different fatty acids revealed that lauric, myristic and linoleic acids were the most potent reducers of methanogenesis (Jordan et al 2006 ;Ding et al 2012 ), and the ability of lauric acid to decrease cell viability of Methanobrevibacter ruminantium has been recently reported by Zhou et al ( 2013 ).…”
Section: Dietary Lipidsmentioning
confidence: 99%
“…Copra meal gives comparable decreases in CH 4 to refi ned coconut oil (Jordan et al 2006 ). Comparison of the effects of different fatty acids revealed that lauric, myristic and linoleic acids were the most potent reducers of methanogenesis (Jordan et al 2006 ;Ding et al 2012 ), and the ability of lauric acid to decrease cell viability of Methanobrevibacter ruminantium has been recently reported by Zhou et al ( 2013 ). A wide range of essential oils (derived from garlic, thyme, oregano, cinnamon, rhubarb, frangula, etc.)…”
Section: Dietary Lipidsmentioning
confidence: 99%